Features of the inducible nitric oxide synthase expression in paraventricular and supraoptic nuclei of hypothalamus in different models of arterial hypertension - Kolesnyk, Yu. M.; Kuzo, N. V.; Hancheva, O. V.; Abramov, A. V.; Колесник, Юрій Михайлович; Кузьо, Назар Володимирович; Ганчева, Ольга Вікторівна; Абрамов, Андрій Володимирович (Zaporozhye state medical university, 2016)
The regulation of the paraventricular (PVN) and supraoptic (SON) nuclei’s activity is carried out with a great amount of different neurotransmitters, in particular, with nitric oxide. In order to get clear understanding of the local NO effects in hypothalamus in normal condition and different models of hypertension it is necessary to study all isoforms of NOS in PVN and SON. Our purpose was to find out the features of the inducible nitric oxide synthase (iNOS) expression in magnocellular SON and PVN in SHR and endocrine-saline model of hypertension in rats. Materials and methods. For all rats the mean blood pressure (mBP) was measured. In Wistar rats mBP was stable during the experiment. In SHR mBP was higher than normal. In animals of the 3 rd group with ESM the first measurement (before the modelling) demonstrated normal rates of mBP. Since the 7th day of modelling mBP started increase and became steadily increased from the 21 st day. We obtained the frontal slices of hypothalamus and performed the assessment of iNOS expression using immunofl uorescence assay. The results showed the presence of the constitutive expression of iNOS in the magnocellular neurons of hypothalamus in Wistar rats as well as in both groups of experimental hypertension. The level of iNOS expression in magnocellular nuclei was dependent both on type of hypertension and topography of magnocellular neurons in hypothalamus. In SHR there was high expression of iNOS in PVN and low one in SON, whereas in endocrine-saline model there was high expression in SON and there were no substantial changes of the iNOS expression in PVN. Conclusions. We believe the alteration of iNOS expression in magnocellular nuclei of hypothalamus could participate in development and/or adaptation to hypertension. Регуляція активності супраоптичного (СОЯ) та паравентрикулярного (ПВЯ) ядер здійснюється внаслідок великої кількості нейротрансміттерів, зокрема оксиду азоту (NO). Вважаємо, що для отримання чіткого розуміння локальних ефектів NO в гіпоталамусі необхідно дослідити експресію всіх ізоформ синтази оксиду азоту в ПВЯ та СОЯ. Мета роботи – встановлення особливостей експресії індуцибельної синтази оксиду азоту (iNOS) у великоклітинних СОЯ та ПВЯ гіпоталамуса в SHR і за умов ендокринно-сольової моделі (ЕСМ) артеріальної гіпертензії в щурів. Матеріали та методи. Усім щурам виміряли середній артеріальний тиск (сАТ). У щурів лінії Wistar сАТ був стабільним протягом експерименту. У щурів лінії SHR сАТ був стабільно підвищений. У щурів ЕСМ до початку моделювання сАТ був нормальним. З 7 доби моделювання сАТ підвищувався та став стабільно підвищеним, починаючи з 21 доби моделювання. Отримали фронтальні зрізи гіпоталамуса та виконали оцінювання експресії iNOS у них за допомогою імунофлуоресцентного аналізу. Результати. Дослідження показало наявність конституційної експресії iNOS у великоклітинних нейронах гіпоталамуса як у щурів лінії Wistar, так і в обох експериментальних моделях. Рівень експресії iNOS у великоклітинних нейронах залежав як від типу моделі, так і від топографічної приналежності великоклітинних нейронів. Так, у SHR високий рівень експресії iNOS був відзначений у ПВЯ, тоді як у СОЯ він був значно нижчим за показники контрольної групи. З іншого боку, за умов ендокринно-сольової моделі значне збільшення експресії iNOS відзначалося в СОЯ, тоді як у ПВЯ ми не знайшли вірогідних змін. Висновки. Зміна рівня експресії iNOS у великоклітинних нейронах гіпоталамуса може брати участь у розвитку та/або адаптації до артеріальної гіпертензії. Регуляция активности супраоптического (СОЯ) и паравентрикулярного (ПВЯ) ядер гипоталамуса осуществляется благодаря большому количеству нейротрансмиттеров, в частности, оксиду азота (NO). Мы считаем, что для получения чёткого понимания локальных эффектов NO необходимо изучить экспрессию всех изоформ синтазы оксида азота в ПВЯ и СОЯ. Цель работы – установление особенностей экспрессии индуцибельной синтазы оксида азота (iNOS) в крупноклеточных СОЯ и ПВЯ гипоталамуса у SHR и в условиях эндокринно-солевой модели (ЭСМ) артериальной гипертензии у крыс. Материалы и методы. Всем крысам было измерено среднее артериальное давление (сАД). У крыс линии Wistar сАД было стабильное на протяжении всего эксперимента. У крыс линии SHR сАД было стабильно повышенным. У крыс ЭСМ до начала эксперимента сАД было нормальным. С 7 суток моделирования сАД начало повышаться и стало стабильно повышенным, начиная с 21 суток моделирования. Мы получили фронтальные срезы гипоталамуса и провели оценку экспрессии iNOS в них с помощью иммунофлуоресцентного анализа. Результаты. Исследование показало наличие конституциональной экспрессии iNOS в крупноклеточных нейронах гипоталамуса как у крыс линии Wistar, так и в обеих моделях экспериментальной гипертензии. Уровень экспрессии iNOS в крупноклеточных нейронах зависел как от типа модели, так и от топографической принадлежности крупноклеточных нейронов. Так, у SHR высокий уровень экс-прессии iNOS отмечался в ПВЯ, в то время как в СОЯ он был значительно ниже показателей контрольной группы. С другой стороны, в условиях эндокринно-солевой модели значительное увеличение экспрессии iNOS отмечалось в СОЯ, в то время как в ПВЯ мы не выявили достоверных отличий. Выводы. Изменение уровня экспрессии iNOS в крупноклеточных нейронах гипоталамуса может принимать участие в развитии и/или адаптации к артериальной гипертензии.
Особливості експресії індуцибельної синтази оксиду азоту в паравентрикулярному та супраоптичному ядрах гіпоталамуса при різних моделях артеріальної гіпертензії
Особенности экспрессии индуцибельной синтазы оксида азота в паравентрикулярном и супраоптическом ядрах гипоталамуса при разных моделях артериальной гипертензии
Keywords: Hypothalamus; Experimental Arterial Hypertension; Rats; Magnocellular Neurons; Nitric Oxide Synthase; Гіпоталамус; експериментальна артеріальна гіпертензія; щури; великоклітинні нейрони; синтаза оксиду азоту; гипоталамус; экспериментальная артериальная гипертензия; крысы; крупноклеточные нейроны; синтаза оксида азота